ACCESS TO LEARNING MATERIALS AND RESOURCES - Erkinova Shahnozaxon Alimjon qizi Student Gaziyeva Saida Turgunovna, (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
Access to quality learning materials and resources is fundamental to equitable and effective education. In many regions, especially in developing countries, students face significant barriers in acquiring necessary textbooks, digital tools, and supplementary materials. This study explores the current state of accessibility to educational resources, the impact of unequal access on learning outcomes, and the strategies employed to overcome these challenges. Drawing on a combination of literature review and interviews with educators and students, the research highlights disparities in resource distribution and the growing importance of digital materials. The findings underscore the urgent need for policy reforms, technological investments, and inclusive educational planning to ensure that every learner has the tools necessary to succeed.